Comparative chromato-mass spectroscopy studies on tinctures of Valeriana stolonifera Czern. - V. M. Odyntsova; V. H. Korniievska; Yu. I. Korniievskyi; V. I. Kokitko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Valerian (Valeriana officinalis L.s.l.) is a flowering plant that includes 13 species in Ukraine. Valeriana stolonifera Czern is the most common of southern species that can be found in the Zaporizhzhia region. The duration and effectiveness of its drying depend on morphological features of Medicinal Herb Raw Material (MHRM), reference humidity, total surface area, thickness and lignification of the roots. Due to the process of dehydration as a result of drying, the increase of active substances in MHRM is sometimes observed. This process is conditionally called a “ripening stage”, or fermentation.